Chronic Benign Tubular Albuminuria From Compound Heterozygous Variants in : A Case Report - Adam Pietrobon; Mark D. Elliott (Canadian Journal of Kidney Health and Disease)
Rationale: Albuminuria is a commonly used parameter for predicting decline in kidney filtration function. Cubilin, encoded by CUBN , is a critical protein involved in protein reabsorption in the proximal tubule. Mutations in CUBN lead to Imerslund-Gräsbeck syndrome (IGS), a disorder characterized by vitamin B12 deficiency (and consequences related to that) with or without albuminuria. Recent evidence suggests that C-terminal variants in CUBN may lead to albuminuria without other features of IGS. Presenting concerns of the patient: Here, we report a case of a 52-year-old male with chronic, albumin-predominant, subnephrotic range proteinuria since his teenage years, but preserved estimated glomerular filtration rate (eGFR). Interventions: Neither angiotensin-converting enzyme (ACE) inhibition nor angiotensin Type II (AT-II) receptor blockade reduced his degree of albuminuria. Diagnosis: Genetic testing identified 3 distinct pathogenic variants in CUBN that were confirmed by segregation analysis to be a compound heterozygous mode of inheritance. All variants were downstream of the intrinsic factor-vitamin B12 binding domain of cubilin. The patient had normal vitamin B12 levels and did not exhibit any features of IGS. Outcomes: Kidney biopsy was not pursued for this patient as diagnostic clarification was achieved by non-invasive genetic testing alone. Novel findings: This case highlights several important lessons. First, not all albuminuria is made equal, and forms of tubular albuminuria can exist without compromising kidney filtration function. Second, identifying genetic forms of tubular albuminuria is key to avoiding ineffective interventions (eg, ACE inhibition, AT-II receptor blockade, sodium-glucose cotransporter-2 [SGLT2] inhibition) and unnecessary invasive procedures (eg, kidney biopsy). Third, the location of CUBN variants dictates phenotypic consequences, with C-terminal variants leading to albuminuria without vitamin B12 deficiency.